Representations of the self and the other through the mask in Al-Sayyab’s poetry - Batoul Moneim Fadel Muhammad/ Ali Abdul Rahim Karim ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Al-Sayyab took steady steps to distance himself from the extravagant lyricism in the poem, and thus different voices entered the poetic work. The elements of artistic techniques in Arabic poetry have been completed, after the lyrical nature prevailed in Arabic poetry for several centuries past, and among those methods was employing the other/mythological, heritage, and religious, and framing it with new frameworks and a new vision. Al-Sayyab’s exposure to foreign literature opened the horizon for change, and it also provided him with the necessary examples for this change. This became clear from the manifestation of foreign influences in his poetic production, as they were more prominent and clear in the early poetic works, but with time they became lost and difficult for the researcher, and this is natural, as the broader and deeper the poetic experience became, the more capable it became of melting the following in the crucible of experience. His belief in the unity of human experience in different eras was evident in Al-Sayyab’s poetry, which made him employ the voices and visions of others, which belong to different eras and trends, trying to give several visions to different characters within the limits of one poem, which gave this poem greater openness to the world of objective expression, to be It is qualified to reveal conflicts that transcend the boundaries of time and place. In addition to that, Al-Sayyab tried to attract elements of heroism in others and pull them into the life he lives, and one of these artistic techniques